Relative age within the school year and diagnosis of attention-deficit hyperactivity disorder: a nationwide population-based study - Sayal, Kapil; Chudal, Roshan; Hinkka-Yli-Salomäki, Susanna; Joelsson, Petteri; Sourander, Andre (Elsevier, 2017)
Background